The Role of Indonesian Service Companies in Implementing Halal Cargo Policy: A Literature Review - Ahmad Waisul Qorony; Atina Shofawati (Universitas Syiah Kuala, 2025)
The global halal industry continues to grow rapidly, with halal logistics playing a critical role in maintaining the halal status of products throughout the distribution process. The halal cargo policy aims to ensure that halal products remain guaranteed throughout the supply chain, including during transportation and storage. In Indonesia, regulations related to the halal cargo policy are outlined in Article 22 of Government Regulation Number 39 of 2021, which regulates halal logistics. However, the implementation of this policy faces several challenges. One of the main challenges is the lack of understanding among service companies regarding the importance of halal certification and how to incorporate it into their logistics systems. In addition, the high costs associated with halal certification and the variation in standards across companies pose significant barriers to policy implementation. This study uses a literature review method to explore the role of service companies in implementing the halal cargo policy in Indonesia. The findings suggest that for successful implementation, there is a need to raise awareness among service companies about the importance of maintaining the halal status of products during distribution. In addition, the development of infrastructure that supports halal logistics, along with the adoption of new technologies such as blockchain and the Internet of Things (IoT), can improve efficiency, transparency, and accountability in managing halal cargo. This study recommends increasing synergy between the government and the service sector to strengthen the implementation of halal cargo policies, which ultimately increases consumer confidence in halal products in the global market.